Comparison between two dosage regimens of enrofloxacin given in drinking water for treatment of induced air sacculitis in chicks - Al- Ani, L. A.; Al-Khayyat, A. A.; Abid, A. H. (The Iraqi Journal of Veterinary Medicine, 2021)
Response to treatment of induced air sacculitis by a pathogenic strain of E coli with enrofloxacin when it was given by the recommended therapeutic concentration (50 mg/ml) for 3 days in drinking water was compared with the method of giving the same drug at double the above concentration for one time after a period of thirstiness . Athird group of infected bird was left without treatment while a non – infected group was left as a negative control . Parameters of mortality , clinical symptoms, feed consumption , weight gain and feed conversion were measured to evaluate the effectiveness of either method of treatment. Also, after sacrifying of some birds one week and 3 weeks after infection, pathological lesions and air sacculitis index were considered. The results showed significant differences in most parameters between infected and non – infected groups while either of the two infected treated groups were intermediate between them. This result encourages the use of the suggested single method of treatment especially when cost of drug, full dosing and stability of drug are taken in consideration